2017
DOI: 10.1080/13607863.2017.1416589
|View full text |Cite
|
Sign up to set email alerts
|

Identifying modifiable factors associated with health optimism in older adults

Abstract: These findings extend the limited evidence on health optimism in older adults by identifying various modifiable factors that may constitute potential areas of focus for future interventions designed to enhance health outcomes via the fostering of health optimism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…"Health optimism" occurs when an individual's self-rated or subjective health is better than their objective health (Chipperfield 1993). Higher levels of psychological well-being and quality of life have been found to be positively associated with health optimism, suggesting that strategies designed to foster these psychological factors have the potential to improve an individual's β = .06, P = .002 β = .06, P = .222 β = .12, P = .020 Social connectedness Perceived value 0.00 0.00 .03 .129 Personal responsibility 0.01 0.00 .07 .001 β = .09, P < .001 β = − .05, P = .438 β = .04, P = .499 Depression Perceived value 0.00 0.00 .02 .161 Personal responsibility 0.01 0.00 .04 .026 β = .05, P = .015 β = .03, P = .670 β = .08, P = .219 Personal growth Perceived value 0.00 0.00 .03 .088 Personal responsibility 0.01 0.00 .07 .001 β = .10, P < .001 β = − .05, P = .462 β = .06, P = .394 Religious attendance Perceived value 0.01 0.01 .01 .202 Personal responsibility 0.04 0.01 .05 < .001 β = .06, P < .001 β = .05, P = .255 β = .11, P = .015 self-rated health (Rai et al 2017). This in turn may increase their propensity to volunteer.…”
Section: Intervention Implicationsmentioning
confidence: 99%
“…"Health optimism" occurs when an individual's self-rated or subjective health is better than their objective health (Chipperfield 1993). Higher levels of psychological well-being and quality of life have been found to be positively associated with health optimism, suggesting that strategies designed to foster these psychological factors have the potential to improve an individual's β = .06, P = .002 β = .06, P = .222 β = .12, P = .020 Social connectedness Perceived value 0.00 0.00 .03 .129 Personal responsibility 0.01 0.00 .07 .001 β = .09, P < .001 β = − .05, P = .438 β = .04, P = .499 Depression Perceived value 0.00 0.00 .02 .161 Personal responsibility 0.01 0.00 .04 .026 β = .05, P = .015 β = .03, P = .670 β = .08, P = .219 Personal growth Perceived value 0.00 0.00 .03 .088 Personal responsibility 0.01 0.00 .07 .001 β = .10, P < .001 β = − .05, P = .462 β = .06, P = .394 Religious attendance Perceived value 0.01 0.01 .01 .202 Personal responsibility 0.04 0.01 .05 < .001 β = .06, P < .001 β = .05, P = .255 β = .11, P = .015 self-rated health (Rai et al 2017). This in turn may increase their propensity to volunteer.…”
Section: Intervention Implicationsmentioning
confidence: 99%
“…Characterised by a U-shape trajectory over the life-course, MWB is high in early life, dips in mid-life, and increases again in older age [ 7 ], when it may be most beneficial to health. Health outcomes of higher MWB include reduced mortality [ 8 ]; increased immune system function, pain tolerance [ 9 ] and physical function [ 10 ]; and improved health optimism [ 11 ] and pro-social behaviour [ 12 ]. Some of these health outcomes are evidenced by studies of psychobiological systems linking positive affect with distinct biological correlates (favourable associations with heart rate, blood pressure, and inflammatory markers such as interleukin-6) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another finding is that objective support and support use are directly and significantly associated with DRSCA and the indirect effect was not significant. It is indicated that there are more powerful factors associated with optimism, such as quality of life and psychological well‐being, which are directly and positively associated (Rai, Jongenelis, Pettigrew, Jackson, & Newton, ); another consideration is that controls will lower the overall power and reduce the power for detecting true mediator effects. Further studies are needed to confirm the mediation of optimism between social support and DRSCA in different situations.…”
Section: Discussionmentioning
confidence: 99%